2007
DOI: 10.1111/j.1440-1819.2007.01701.x
|View full text |Cite
|
Sign up to set email alerts
|

Residential program for long‐term hospitalized persons with mental illness in Japan: Randomized controlled trial

Abstract: Research on the merits of long-term group residences is inconclusive. The purpose of the present paper was to investigate the effects of supported group residence on the symptoms, social function, quality of life, general health quality, and the medical/psychiatric cost in Japan of a large number of psychiatric beds and long average length of stay. Patients were assessed every 6 months for 2 years using Positive and Negative Syndrome Scale, Katz Adjustment Scale, World Health Organization Quality of Life (WHO-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
45
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(45 citation statements)
references
References 29 publications
0
45
0
Order By: Relevance
“…Residents in the community were provided with access to social skills training and rehabilitation group activities including occupational therapy on-site as well as at a day care program [47]. Chan et al (2007) noted that there was an overall trend towards improvement in both positive and negative symptoms amongst the residents over a two-year period [47]. Consistent with other studies, improvement over this time was noted in social functioning and QoL [47].…”
Section: Recent Studies Of Outcomes Of Community Mental Health Carementioning
confidence: 70%
See 2 more Smart Citations
“…Residents in the community were provided with access to social skills training and rehabilitation group activities including occupational therapy on-site as well as at a day care program [47]. Chan et al (2007) noted that there was an overall trend towards improvement in both positive and negative symptoms amongst the residents over a two-year period [47]. Consistent with other studies, improvement over this time was noted in social functioning and QoL [47].…”
Section: Recent Studies Of Outcomes Of Community Mental Health Carementioning
confidence: 70%
“…Chan et al (2007) reported on the transition of former long-stay patients to a purpose-built supported group residence in Kochi, Japan, with a capacity to house up to 20 residents [47]. Residents in the community were provided with access to social skills training and rehabilitation group activities including occupational therapy on-site as well as at a day care program [47]. Chan et al (2007) noted that there was an overall trend towards improvement in both positive and negative symptoms amongst the residents over a two-year period [47].…”
Section: Recent Studies Of Outcomes Of Community Mental Health Carementioning
confidence: 97%
See 1 more Smart Citation
“…In the psychiatry population, several studies have examined the psychometric properties of QOL questionnaires, but these studies primarily include outpatients [4,26,27] or less disabled inpatients [28][29][30], and thus only examine those with a relatively narrow spectrum of symptoms, functional status, and cognitive impairment. An exception is the study that examined long-stay patients in a psychiatric hospital and showed that only 26% of the patients were able to answer the World Health Organization Quality of Life (WHOQOL), a questionnaire about QOL [13].…”
Section: Discussionmentioning
confidence: 99%
“…The current study obtained similar outcomes. [23][24][25] Research results indicated that women perform better than men in daily life skills and treatment compliance. Based on these outcomes, it can be said that female patients are in a better position than male patients to meet the needs of daily life; furthermore, they attach more importance to therapy.…”
Section: Discussionmentioning
confidence: 99%